Characteristics of lightning‐induced voltages based on experimental data. Issue 3 (9th December 2020) - Santos, Michele N. N.; Piantini, Alexandre
Abstract: This paper presents an analysis of 64 lightning‐induced voltage waveforms recorded in an experimental system implemented in the campus of the University of São Paulo, Brazil. The voltages were measured on a 10 m high, 2.7 km long un‐energized overhead line consisting of two conductors installed on 6 m crossarms. One of the conductors had surge arresters, while the other one was left unprotected. Strictly speaking, all the recorded voltages on the unprotected conductor were bipolar, but in many cases only one semi‐cycle could be considered important for practical purposes. Different criteria are discussed for the determination of the waveshape parameters, which may differ significantly from those of the standard lightning impulse voltage (1.2/50 μs). Based on the proposed criterion for classifying the induced voltages, unipolar waveforms accounted for 67% of the total and, except for one case, all of them had positive polarity. The median values of the front time and time‐to‐half‐value were, respectively, 5.2 μs and 15.8 μs. Bipolar waveforms were 33% of the total and in approximately 62% of the cases the first semi‐cycle was of positive polarity. In 91% of the cases the voltage peak occurred either in the first or the second semi‐cycle.